2016
DOI: 10.1136/bmjopen-2016-011060
|View full text |Cite
|
Sign up to set email alerts
|

Utility of models to predict 28-day or 30-day unplanned hospital readmissions: an updated systematic review

Abstract: ObjectiveTo update previous systematic review of predictive models for 28-day or 30-day unplanned hospital readmissions.DesignSystematic review.Setting/data sourceCINAHL, Embase, MEDLINE from 2011 to 2015.ParticipantsAll studies of 28-day and 30-day readmission predictive model.Outcome measuresCharacteristics of the included studies, performance of the identified predictive models and key predictive variables included in the models.ResultsOf 7310 records, a total of 60 studies with 73 unique predictive models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
217
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(245 citation statements)
references
References 92 publications
13
217
0
6
Order By: Relevance
“…Recent years have seen an explosion in these predictive models, which use patterns observed within large data sets to generate readmission risks for individual patients. In 2011, a systematic review found 26 models for readmissions,3 but an updated review that examined papers published up to 2015 found 68 more 4…”
mentioning
confidence: 99%
“…Recent years have seen an explosion in these predictive models, which use patterns observed within large data sets to generate readmission risks for individual patients. In 2011, a systematic review found 26 models for readmissions,3 but an updated review that examined papers published up to 2015 found 68 more 4…”
mentioning
confidence: 99%
“…[32] Zhou et al reviewed unplanned readmission risk models in detail in 2016. [51] The review emphasized classification of predictors and performance attributes of the 73 published models across 60 studies, and discrimination (AUROC) and calibration (Hosmer Lemeshow – only if reported) were compared. The state of the literature leaves a significant gap for more frequent inclusion of usefulness analyses as the decision-analytic framework prior to changing clinical workflow requires them.…”
Section: Discussionmentioning
confidence: 99%
“…[8], [19] However, clinical adoption of risk prediction models remains quite low. [20], [21] Some of the barriers reported by physicians for not using risk prediction models are lack of time, lack of trust in its validity, and uncertainty about generalizability to the specific patient population seen by an individual physician.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Hospital readmission risk prediction models have been traditionally developed using hypothesis-driven statistical methods since 1980s; and as of 2015, at least 94 unique models had been described in the published literature. [8], [9] Although these risk prediction models are helpful decision making tools, their utility is limited by considerations of generalizability, adaptability and absolute predictive performance. First, most of these models have been developed using high quality data from select patient cohorts, and therefore can have inconsistent external validity in other settings and patient populations, in the setting of missing data and over time.…”
Section: Introductionmentioning
confidence: 99%